Expressão imuno-histoquimica da cicloxigenase-2 e p53 em cancinoma epidermóide oral - Goulart Filho, João Augusto Vianna (2006)
Squamous cell carcinoma is the most common malignant neoplasm in the oral cavity, accounting for more than 90% of all malignancies in this location. Cyclooxygenases (COX s) are key enzymes on arachidonic acid metabolism and prostaglandin synthesis, being expressed basically in two forms: the constitutive (COX-1) and the inducible (COX-2). Increased levels on the expression of COX-2 have been implicated in the pathogenesis tumor progression of various forms of human cancer, including oral squamous cell carcinoma, some of what suggesting a possible interaction between COX-2 and the protein expressed by the tumor suppressor gene p53, mutated in more than 50% of all human cancers. The mean of the present research consisted in analyze the correlation between the expression of COX-2 and p53, at the protein level, as well as evaluate the difference on the expression of these two proteins with the histological grading of malignancy. 34 cases of oral squamous cell carcinoma were selected and graded according to the histological grading system proposed by Bryne (1998) and the labeling indexes (LI s) for COX-2 and p53 evaluated using immunohistochemistry method. The results revealed that COX-2 was expressed in increased levels in most of the specimens, although there was no statistic significant correlation between LI s from COX-2 and p53 (p>0.05), and there were no statistical differences on the expression of these proteins between tumors of high and low grade of malignancy (p>0.05). Interestingly, the expression of COX-2 and p53 was detected in fragments of dysplastic oral epithelium adjacent to tumor areas, on basal and suprabasal layers. The absence of statistical correlation between the expression of COX-2 and p53 proteins do not rule ot the existence of a relation between them, were it may reflect the diversity of regulatory pathways between both, different direct and indirect inhibitory effects of COX-2 over p53, as well as the wide range of activation macheenisms for COX-2 and mutational status of the p53 gene Another conclusion point that the increased expression of COX-2 observed in oral squamous cell carcinomas suggest a role for this protein in the processes of pathogenesis and tumoral evolution of this malignant neoplasm